Who are the Behavioral Economists and what do they say? - Floris Heukelom (Tinbergen Institute, 2007)
The most important financial source for behavioral economics is the Russell Sage Foundation (RSF). The most prominent behavioral economists among the RSF's twenty-six member Behavioral Economics Roundtable (BER) are Kahneman, Tversky, Thaler, Camerer, Loewenstein, Rabin, and Laibson. The theoretical core of behavioral economics made up of the work of these seven researchers is positioned in opposition to Adam Smith/Hayek type of economics, as exemplified by experimental economists Vernon Smith and Plott; and what is referred to as `mainstream' or `traditional' economics, meaning the neoclassical economics that roughly builds on Samuelson. On the basis of an overview of the work of these seven behavioral economists, a theoretical division can be observed within behavioral economics. The first branch considers human decision-making to be a problem of exogenous uncertainty, which can be analyzed with decision theory. It employs traditional economics as a nor! mative benchmark and favors a normative-descriptive(-prescriptive) distinction for economics. The second branch considers human decision-making to be a problem of strategic interaction, in which the uncertainty is endogenous. Its main tool is game theory. It rejects traditional economics both positively and normatively.
Keywords: A12; B21; B31; D0; 330; Behavioral economics; Russell Sage Foundation; experimental economics; Kahneman; Tversky; Thaler; Laibson; Loewenstein; Rabin; Camerer; Verhaltensökonomik; Ökonomen